Toxic impacts of titanium dioxide nanoparticles in Mytilus galloprovincialis exposed to warming conditions - Leite, Carla Patrícia da Silva (2019)
Titanium dioxide nanoparticles (TiO2 NPs) have been widely used in various industrial applications and consumer products. Due to their large production and use, they will eventually enter into aquatic environment. Once in the aquatic environment TiO2 NPs may interact with the organisms and induce toxic effects. Beside contamination, organisms are also exposed to climate change, responsible for a gradual increase in the ocean temperature, which can cause physiological and biochemical impairments in aquatic organisms as well as increased the sensibility of organisms to pollutants. Furthermore, it is already reported that warming may change the properties and toxicity of pollutants. Since the most common forms of TiO2 NPs are rutile and anatase, the present study evaluated the effects of these two forms in Mytilus galloprovincialis at control temperature and the effects of rutile NPs under warming conditions. For this, mussels were distributed into two climatic rooms to maintain organisms at two different temperatures: 18±1 and 22±1 °C. The tested concentrations of rutile and anatase NPs at 18 °C and of rutile ate 22 °C were 0 μg/L; 5 μg/L; 50 μg/L; and 100 μg/L. The experimental exposure lasted 28 days and at the end Ti concentrations, histopathological alterations and biochemical effects were evaluated. Histopathological results demonstrated that both forms of TiO2 induced alterations on gills and digestive glands along the increasing exposure concentrations regardless the temperature. Biochemical markers showed that mussels exposed to rutile NPs at control temperature maintained their metabolic capacity (assessed by the activity of the electron transport system, ETS), while the metabolism of mussels exposed rutile NPs under higher temperature increased at 5 and 50 μg/L of Ti and in mussels exposed to anatase NPs the metabolic capacity was increased. Mussels exposed to rutile NPs at control temperature increased their detoxificant defenses which, due to the low tested concentrations, were sufficient to avoid cellular damage. On the other hand, mussels exposed to anatase NPs suffered cellular damages despite the increased in antioxidant defenses which may be related to higher activity of the electron transport system. Also, mussels exposed rutile NPs under higher temperature activated the antioxidant defenses, however still cellular damage occurred under these conditions. Overall, this study showed that rutile and anatase NPs were toxic to M. galloprovincialis, with higher oxidative stress exerted by anatase form and that temperature rise may significantly increase the sensitivity of bivalves towards rutile NPs, revealing higher toxic impacts in mussels exposed to rutile NPs under warming conditions.